Orientalisme sebagai Tradisi Keilmuan dalam Pandangan Maryam Jameelah dan Edward Said - Yuangga Kurnia Yahya; Syamsul Hadi Untung; Umi Mahmudah (JIA (Jurnal Ilmu Agama), 2020)
This article talks about orientalism. Orientalism is a scientific tradition and discipline that examines all matters relating to the East from a Western perspective. Unfortunately, the Western perspective and framework that is superior to the inferior East influences most of the results of the study. The author uses the criticism of Maryam Jameelah and Edward Said in seeing how Orientalism works. Both figures were chosen because of their unique religious, ethnic and racial background. Both have felt the atmosphere of life in the East (Palestine and Pakistan) and also in the West (America). Therefore, they are expected to be able to provide comments and views related to how Orientalism works. At the end, the author lists the attitude of the East man in addressing the results of the study of the orientalists, namely with a critical receptive attitude and not trapped with a receptive and rejective attitude through all results of study.